Carlos Sere on the development of ILRI's research agenda 2002–2021 - Seré Rabé, Carlos (International Livestock Research Institute, 2021)
Carlos Sere, ILRI director general 2002–2011, speaks about the evolution of the ILRI research agenda and how the institute has responded to development challenges. Read more about ILRI's impact book which covers over 45 years of research for better lives through livestock: ilri.org/ILRI-research-impact